The Role of Job Placement, Promotion, and Intellectuality in Improving the Performance of Employees of the North Labuhanbatu Regency Education Office - Gusmiati, Yesi; Nadya, Mirfat; Bayan, Sri; utarbutar, Dyanti SR; Syahputra, Rahmat Akbar; Safrida, Safrida (Journal of Finance and Business Digital, 2024)
In government agencies, such as the North Labuhanbatu Regency Education Office, improving employee performance is a central issue that continues to be studied to improve the quality of public services This study aims to analyze the influence of job placement, promotion, and intellectuality on employee performance at the North Labuhanbatu Regency Education Office. The research method uses a quantitative approach with a questionnaire survey of 100 employees. Data analysis was carried out by Pearson correlation test and multiple linear regression. The results of the study show that these three variables have a significant effect on employee performance, both partially and simultaneously. Intellectuality has the greatest influence, followed by job placement and promotion. Thus, intellectual development, appropriate placement, and a fair promotion system prove to be important in improving employee performance.